Does democracy facilitate the economic transition? : an empirical study of Central and Eastern Europe and the Former Soviet Union - Dethier, Jean-Jacques, 1952- 1952- (Policy research working paper, 1999)
Empirical analysis shows that democracy has facilitated economic liberalization in 25 postcommunist countries of Central and Eastern Europe and the former Soviet Union. The existence of a vibrant civil society at the start of the transition has the most explanatory power in this team's regression